2022
DOI: 10.3390/molecules27175486
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Preparations from the Leaves of Wild Plant Species of the Genus Rubus

Abstract: The plants of the genus Rubus (R.) are applied as antiseptic agents in the treatment of skin diseases. Despite the great interest in plants of this genus, there are few reports on the antioxidant and biological activities of preparations obtained from the leaves of these plants. Therefore, we decided to evaluate the antioxidant activity of preparations from leaves of wild plant species of the genus Rubus using the frequently applied DPPH, ABTS, and FRAP methods, as well as to determine the total polyphenol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…However, the antimicrobial and antiviral properties of plants have also begun to be more actively researched after the breakthrough in packaging production in recent years, as evidenced by various research studies on films [ 31 , 32 ]. Kucharskii et al [ 33 ] stated that the raspberry leaves of the genus Rubus can be applied as antiseptic agents in the treatment of skin diseases. The biological action exerted by the R.idaeus leaf hydrolate, investigated by De Santis et al, was observed on B. cereus and A. bohemicus strains [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the antimicrobial and antiviral properties of plants have also begun to be more actively researched after the breakthrough in packaging production in recent years, as evidenced by various research studies on films [ 31 , 32 ]. Kucharskii et al [ 33 ] stated that the raspberry leaves of the genus Rubus can be applied as antiseptic agents in the treatment of skin diseases. The biological action exerted by the R.idaeus leaf hydrolate, investigated by De Santis et al, was observed on B. cereus and A. bohemicus strains [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The core of liposomes is a droplet of water. Wettability studies showed that all bio-ferments are highly hydrophilic and can accumulate in lipid bilayers in the aqueous core of liposomes [33].…”
Section: Discussionmentioning
confidence: 99%
“…The FRAP technique assessed the antioxidant activity of the bio-ferments obtained (B-P, B-E, B-O, and B-S) [33]. These studies used the Thermo Scientific GENESYS 50 instrument at the wavelength λ = 593 nm.…”
Section: Frap Methodsmentioning
confidence: 99%
“…In order to assess the antioxidant capacity of silymarin, bio-ferment, and extract, the FRAP method was used [35]. The analyses were performed on the Thermo Scientific GENESYS 50 apparatus at the wavelength λ = 593 nm.…”
Section: Frap Methodsmentioning
confidence: 99%